1987
DOI: 10.1073/pnas.84.23.8370
|View full text |Cite
|
Sign up to set email alerts
|

cDNA sequence, protein structure, and chromosomal location of the human gene for poly(ADP-ribose) polymerase.

Abstract: Recently we described a full-length cDNA for the human nuclear enzyme poly(ADP-ribose) polymerase. Here, we report the chromosomal localization and partial map of the human gene for this enzyme as well as the complete coding sequence for this protein. The nucleotide sequence reveals a single 3042-base open reading frame encoding a protein with a predicted Mr of 113,135. A comparison of this deduced amino acid sequence with the amino acid sequence of three peptides derived from human poly(ADP-ribose) polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
75
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(78 citation statements)
references
References 22 publications
3
75
0
Order By: Relevance
“…Reprobing of the immunoblot with antibodies to E2F-1 revealed a B60-kDa band, distinct from the 4114 kDa band detected with anti-PAR (Figure 2 right panel), thus, indicating that the modified protein was not E2F-1. PARP-1 is the main acceptor in these reactions, attributable to the presence of up to 28 automodification sites in the protein (Kawaichi et al, 1981;Cherney et al, 1987;Desmarais et al, 1991). In contrast to E2F-1, we have demonstrated that GST-p53 is an effective substrate for PARP-1 under the same conditions (Simbulan- Rosenthal et al, 2001).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Reprobing of the immunoblot with antibodies to E2F-1 revealed a B60-kDa band, distinct from the 4114 kDa band detected with anti-PAR (Figure 2 right panel), thus, indicating that the modified protein was not E2F-1. PARP-1 is the main acceptor in these reactions, attributable to the presence of up to 28 automodification sites in the protein (Kawaichi et al, 1981;Cherney et al, 1987;Desmarais et al, 1991). In contrast to E2F-1, we have demonstrated that GST-p53 is an effective substrate for PARP-1 under the same conditions (Simbulan- Rosenthal et al, 2001).…”
Section: Resultsmentioning
confidence: 94%
“…PARP-1, the most abundant and most extensively studied member of this family, is activated allosterically by binding to DNA ends and plays essential roles in various nuclear processes Menissier-de Murcia et al, 1989). PARP-1 undergoes extensive autopoly(ADP-ribosyl)ation in a central automodification domain (Kawaichi et al, 1981;Cherney et al, 1987). PARP-2 and PARP-3 (Johansson, 1999) apparently account for the residual PARP activity in PARP-1-deficient cells (Shieh et al, 1998;Ame et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…38 In bacteria, they are central to the reversal of the acyl modifications of enzymes such as propionyl-CoA synthetase, which generates the substrate for the acyl modification in the first place. 39 Both the free and the ligated ADP-ribose moieties and its various derivatives serve as targets for recognition by specialized binding domains such as the PARP finger, a treble clef domain that binds polyADP ribose, 40,41 and the Macro 42 and inactive Nudix domains. 38 Some Macro domains also function as enzymes that hydrolyze ADP ribose derivatives, such as polyADP ribose chains 43 or OAADPR.…”
Section: Introductionmentioning
confidence: 99%
“…PARP-1 has been implicated in the DNA damage response as well as in cell growth, regulation, and apoptosis (2)(3)(4). The structure of the 113 kDa PARP-1 protein consists of three functional domains: the DNA binding domain, the central automodification domain, and the catalytic domain (5,6). The N-terminal DNA binding domain (DBD) contains two zinc fingers that recognize and bind to single and double-stranded DNA breaks (7,8).…”
mentioning
confidence: 99%
“…However, PARP-1 can also bind to supercoiled DNA (9), cruciform structures (10), DNA loops (9), and base unpaired regions (11). The central automodification domain is an acceptor of ADP-ribose polymers, and the N-terminus is part of the automodification domain containing a leucine-zipper motif that may be responsible for protein-protein interactions (12,6,13). A catalytic domain is located in the C-terminal fragment, and catalyzes the formation of the branched ADP-ribose polymers from NAD 1 (6,14).…”
mentioning
confidence: 99%